Ecotheology: The Basic Values Of Indonesian Islamic Student Movement (PMII) - Zahid, A. (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2021)
The thinking foundation of a movement is determined by the built ideology, one of the early foundations in a movement,the role of ideology is very important in shaping the characteristics and direction of a movement. Similar with the Indonesian Islamic Student Movement (PMII), ideologically, it is based on ahlussunnah waljama’ah. The ideology of the PMII movement is viewed in the form of the Basic Values of Movement (NDP) which are affirmed in the concept of; monotheism, hablumminallah, hablum minannas, and hablum minal alam. The NDP is what shapes the characteristics of the student movement organization which is expectedto be the answer to current problems. The NDP as a reference in the movement conforms the Islamic ummah guidelines, namely Al-quran and hadith, therefore, the essence of the guidelines is reflected in the Basic Values of Movement. The harmony of religious teachings and the ideology of the movement forms a tangent to the discussion of ecotheology. Ecotheology is present in a combination of two scientific clusters, namely ecology and theology, and is expected to provide scientific contributions in accordance with environmental theology, or the relationship between religious teachings and the environment.Keywords: Basic Values of Movement, PMII, Ecotheology